2000
DOI: 10.1080/10715760000301441
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of nitric oxide on the induction of cytochrome P450 3A4 mRNA by 1,25-dihydroxyvitamin D3in Caco-2 cells

Abstract: Cytochrome P450 (CYP)-dependent drug metabolism decreases in vivo and in cultured hepatocytes under various immunostimulatory conditions. Nitric oxide (NO) released during inflammation is presumed to be involved in this phenomenon. CYP3A4, which is abundant in the liver and small intestine and participates in the metabolism of various drugs, is known to be induced by 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) in the colon carcinoma cell line Caco-2. In this study we examined whether NO affected CYP3A4 gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…CYP3A4 expression was suppressed at the RNA level in cells exposed to the NO donor, which is consistent with previous work in Caco-2 cells, a human colon carcinoma cell line, in which NO donors inhibited the induction of CYP3A4 mRNA by 1,25-dihydroxyvitamin D3 [25,26]. The mechanism of the effect in Caco-2 cells apparently involves the induction of c-myc, which represses CYP3A4 transcription [26].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…CYP3A4 expression was suppressed at the RNA level in cells exposed to the NO donor, which is consistent with previous work in Caco-2 cells, a human colon carcinoma cell line, in which NO donors inhibited the induction of CYP3A4 mRNA by 1,25-dihydroxyvitamin D3 [25,26]. The mechanism of the effect in Caco-2 cells apparently involves the induction of c-myc, which represses CYP3A4 transcription [26].…”
Section: Discussionsupporting
confidence: 79%
“…NO donors can down-regulate CYP mRNAs and proteins in colon carcinoma [25,26] and hepatocarcinoma [27] cell lines, and it was reported that in HT-29 cells, NOS2 inhibitors or antisense oligonucleotides could block the down-regulation of CYP3A4 protein by ceramide [28], a putative mediator of the effects of pro-inflammatory cytokines on CYP expression [29]. We are aware of one published study on the regulation of CYP expression by physiological or pharmacological NO in primary human hepatocytes, which is the optimal system to study regulation of the human drug-metabolizing CYPs.…”
Section: Introductionmentioning
confidence: 99%
“…Carlson and Billings (1996) also demonstrated that the suppression of CYP1A2 and CYP2B1/2 by cytokines is largely prevented by NOS inhibitors and that exogenous NO down-regulates these P450s. We reported that 1,25-dihydroxyvitamin D 3 -induced CYP3A4 gene expression in human colon carcinoma Caco-2 cells is inhibited by NO donors (Hara et al, 2000). These results suggested that NO plays an important role in the regulation of P450, but the mechanism of this effect is unknown.…”
mentioning
confidence: 76%
“…The nuclear receptor, pregnane X receptor, is known to contribute to the CYP3A4 gene induction by these drugs Lehmann et al, 1998;Goodwin et al, 1999). It has recently been demonstrated that 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) is a potent inducer of the CYP3A4 gene in the human colon carcinoma cell line Caco-2, which has been extensively used as an experimental model of small intestinal cells (Schmiedlin-Ren et al, 1997;Hara et al, 2000).…”
mentioning
confidence: 99%
“…The nuclear receptor, pregnane X receptor, is known to contribute to the CYP3A4 gene induction by these drugs Lehmann et al, 1998;Goodwin et al, 1999). It has recently been demonstrated that 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) is a potent inducer of the CYP3A4 gene in the human colon carcinoma cell line Caco-2, which has been extensively used as an experimental model of small intestinal cells (Schmiedlin-Ren et al, 1997;Hara et al, 2000).1,25(OH) 2 D 3 , the most active metabolite of vitamin D, functions to regulate cellular proliferation and differentiation and calcium homeostasis in the intestine, bone, and kidney (Christakos et al, 1996). Most of these physiological activations are mediated by the vitamin D receptor (VDR), which belongs to the nuclear hormone receptor superfamily.…”
mentioning
confidence: 99%